1996
DOI: 10.1111/j.1475-097x.1996.tb01020.x
|View full text |Cite
|
Sign up to set email alerts
|

TECHNICAL NOTE: Continuous non‐invasive measurement of mean blood pressure in fingers by volume‐clamp and differential oscillometric method

Abstract: The present study compares two different methods for non-invasive beat-to-beat finger arterial blood pressure monitoring. The measurements using the volume clamp method (FINAPRES, Ohmeda, USA) were compared with measurements applying the differential oscillometric method (UT9201 device, University of Tartu). 13 healthy volunteers were studied at rest, during head-up tilt (HUT) and during deep breathing (DB) with a fixed rate of 6 breaths/min. Blood pressure was recorded from adjacent fingers of the right hand.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…This can occur as a result of pulse wave re ection in the nger arterial system. During the speci c tests such as single deep breathing or the cold stress test, the oscillometric method-based nger mean blood pressure tended to be overestimated [15].…”
Section: Discussionmentioning
confidence: 99%
“…This can occur as a result of pulse wave re ection in the nger arterial system. During the speci c tests such as single deep breathing or the cold stress test, the oscillometric method-based nger mean blood pressure tended to be overestimated [15].…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier studies (Jagomägi et al. , 1996, 2001) have shown that the finger mean blood pressure changes at rest or during light physical exercise were similarly tracked by the two blood pressure monitors (Finapres and UT9201).…”
Section: Methodsmentioning
confidence: 97%
“…Beat‐to‐beat finger volumetric pulses were measured by the UT9201 physiograph. Being originally constructed for finger mean blood pressure measurement (Reeben & Epler, 1983; Jagomägi et al. , 1996, 2001; Raamat et al.…”
Section: Methodsmentioning
confidence: 99%
“…The last procedure was conditioned by difficulties in the synchronization of data series obtained by the two devices and has been proved in our previous studies [16,17].…”
Section: Signal Processing and Data Analysismentioning
confidence: 99%